Role Play and its Applications - Jacob Gershoni (Forum for Group Psychotherapies and Processes)
Scholars in various disciplines have studied applications of role playing into their chosen fields in psychology and social sciences. Their explorations of role play have spanned over a century. Yet, most colleges, universities, and mental health training institutions devote little effort to teaching role play in a systematic fashion, ignoring this set of skills, its deep roots and vast potential to enhance the work of professionals in psychotherapy, counseling, coaching, and education. This article sets out to survey some of the prominent social scientists whose writings described and helped shape role playing as an important cluster of techniques that may be applied to a wide variety of theoretical schools of thought. After reviewing different theories on role playing, this article describes the process and techniques as we have implemented at the Sociometric Institute in New York.